Cultivating Disgust: Prospects and Moral Implications. (April 2021) - Kurth, Charlie
Is disgust morally valuable? The answer to that question turns, in large part, on what we can do to shape disgust for the better. But this cultivation question has received surprisingly little attention in philosophical debates. To address this deficiency, this article examines empirical work on disgust and emotion regulation. This research reveals that while we can exert some control over how we experience disgust, there's little we can do to substantively change it at a more fundamental level. These empirical insights have revisionary implications both for debates about disgust's moral value and for our understanding of agency and moral development more generally.